2019
DOI: 10.1002/jctb.6141
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ethanol production from lignocellulosic hydrolysates by inhibiting the hydrogen synthesis in Thermoanaerobacterium aotearoense SCUT27(Δldh)

Abstract: BACKGROUND Thermophilic anaerobic bacteria have gained increased interest as a desirable biological catalyst for bioethanol production from lignocellulosic biomass. However, by‐products such as lactic acid, acetic acid and hydrogen (H2) not only lead to low ethanol yield but also increase the difficulty of ethanol purification. Considering that ethanol production is dependent on the supply of NADH, blocking or inhibiting lactic acid (by knocking out ldh) and H2 formation should be a reliable strategy to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In addition, fructose metabolism might be accelerated by overexpression of fructose metabolic genes or deletion of the potential transcriptional repressor [ 60 ]. As T. aotearoense SCUT27 has the great ability to utilize pentose [ 23 , 24 , 61 ], the waste of sugar refinery molasses and sugarcane bagasse hydrolysate (containing sucrose, glucose, fructose, xylose, arabinose and so on) could be co-utilized for biofuels production. Furthermore, co-cultured with other cellulolytic strains, such as C. thermocellum , T. aotearoense SCUT27 may make full use of molasses, bagasse and straw to achieve the maximum benefit.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, fructose metabolism might be accelerated by overexpression of fructose metabolic genes or deletion of the potential transcriptional repressor [ 60 ]. As T. aotearoense SCUT27 has the great ability to utilize pentose [ 23 , 24 , 61 ], the waste of sugar refinery molasses and sugarcane bagasse hydrolysate (containing sucrose, glucose, fructose, xylose, arabinose and so on) could be co-utilized for biofuels production. Furthermore, co-cultured with other cellulolytic strains, such as C. thermocellum , T. aotearoense SCUT27 may make full use of molasses, bagasse and straw to achieve the maximum benefit.…”
Section: Resultsmentioning
confidence: 99%
“…Strains with a deletion of the hfs genes exhibited a 95% decrease in both hydrogen and acetic acid production, and hfsB seemed as the most important gene of the operon hfsABCD [110]. The genes hyd, ech and hfsABCD, highly homologic to that of T. saccharolyticum and T. tengcongensis, were also found in strain SCUT27 and proved to be related to H2 production by gene knockout [112].…”
Section: H2 Productionmentioning
confidence: 99%
“…Shaw et al investigated three putative hydrogenase enzyme systems in T. saccharolyticum and found that the strain with specified hfs and ldh deletions exhibited an increased ethanol yield from consumed carbohydrates [110,111]. The deletion of hfsB was also performed in strain SCUT27 and results indicated the enhanced ethanol production was obtained, due to the increased NADH supply and alcohol dehydrogenase activity [112]. Pyruvate formate lyase-activating protein (PflA) could assist the formation of pyruvate formate lyase (Pfl), which catalyzed pyruvate into acetyl-CoA and formate.…”
Section: Ethanol Productionmentioning
confidence: 99%
See 1 more Smart Citation